2007
DOI: 10.3892/ijo.30.1.217
|View full text |Cite|
|
Sign up to set email alerts
|

Constitutive activation of MAPK/ERK inhibits prostate cancer cell proliferation through upregulation of BRCA2

Abstract: Abstract. BRCA2 is central to an utterly diverse biological behavior elicited after integrin-mediated normal and prostate cancer cell adhesion to basement membrane (BM) and extracellular matrix (ECM) proteins. Unlike normal cells, adhesive stimuli in cancer cells activate PI 3-kinase/AKT signaling resulting in BRCA2 degradation and unchecked cancer cell proliferation and metastasis. However, the precise mechanisms involved in normal BRCA2 homeostasis are unknown. We investigated ERK and AKT phosphorylation in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
36
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 25 publications
(37 citation statements)
references
References 38 publications
1
36
0
Order By: Relevance
“…By using PCa cell lines, a recent study 16 demonstrated that the Skp1-cullin-F-box ubiquitin ligase Skp2 interacts with and promotes ubiquitination of BRCA2, targeting it for degradation in the proteasome; in addition, the loss of BRCA2 promotes PCa cell proliferation and invasion. [15][16][17][18] However, although experimental models based on cultured cell lines are amenable for the assessment of signaling cascades and molecules that are selectively deregulated in cancer, in vivo validation remains a stepping stone in translating relevant scientific findings to the patients' bedside. In the current study, we investigated whether the expression of Skp2 correlates with BRCA2 protein levels in prostate epithelial neoplasms in vivo; we also assessed the functional role of Skp2 overexpression and loss of BRCA2 protein in the early stages of prostate neoplastic transformation.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…By using PCa cell lines, a recent study 16 demonstrated that the Skp1-cullin-F-box ubiquitin ligase Skp2 interacts with and promotes ubiquitination of BRCA2, targeting it for degradation in the proteasome; in addition, the loss of BRCA2 promotes PCa cell proliferation and invasion. [15][16][17][18] However, although experimental models based on cultured cell lines are amenable for the assessment of signaling cascades and molecules that are selectively deregulated in cancer, in vivo validation remains a stepping stone in translating relevant scientific findings to the patients' bedside. In the current study, we investigated whether the expression of Skp2 correlates with BRCA2 protein levels in prostate epithelial neoplasms in vivo; we also assessed the functional role of Skp2 overexpression and loss of BRCA2 protein in the early stages of prostate neoplastic transformation.…”
Section: Discussionmentioning
confidence: 99%
“…6 -8 In addition to cancer predisposition, recent clinical evidence suggests that patients with PCa who carry germline BRCA2 mutations display a more aggressive phenotype with worse survival rates than noncarrier patients 9 -14 ; we have provided mechanistic evidence demonstrating that loss of BRCA2 pro-motes PCa cell proliferation and invasion in experimental cell-line models. [15][16][17][18] These latter findings are important despite the fact that mutations in BRCA2 are rare in sporadic PCas 2,9,19,20 ; in sporadic prostate tumors, nonmutational functional inactivation of BRCA2 may occur through different mechanisms, including down-regulation of its expression. [15][16][17][18]21 Indeed, there is preliminary evidence indicating that BRCA2 protein is significantly reduced in most sporadic PCas.…”
mentioning
confidence: 98%
See 2 more Smart Citations
“…Proteins in the MAPK signalling pathways are activated by both RTKs and TNFα, which allows cells to integrate multiple signals. [8][9][10][11][12][13][14][15][16][17][18][19][20]. ) by converting acidic peptides to methyl esters but increasing the spectra complexity and requiring lyophilization of the sample, which causes adsorptive losses of especially phosphopeptides [28].…”
Section: General Principles Of Signalling Pathwaysmentioning
confidence: 99%